Transdermal permeation effect of collagen hydrolysates of deer sinew on mouse skin, ex vitro, and antioxidant activity, increased type I collagen secretion of percutaneous proteins in NIH/3T3 cells. (20th June 2019) - Zhang, He; Pan, Daian; Dong, Ying; Su, Wenjie; Su, Hang; Wei, Xinghua; Yang, Chunhui; Jing, Li; Tang, Xiaolei; Li, Xiangyan; Zhao, Daqing; Sun, Liwei; et al.
Abstract: Background: The collagen hydrolysates as a cosmetic material have already been wide application. At present, few studies concern with transdermal behavior of collagen hydrolysates in vitro. Objective: Deer sinew contains rich collagen with a content of 82.12%. Thus, this article mainly studies the transdermal effect of collagen hydrolysates of deer sinew (DSCH) on mouse skin, ex vitro, and to explore skincare protection of percutaneous proteins. Methods: Collagen hydrolysates of deer sinew were extracted by 0.2% HCl and a two‐step enzymatic method of pepsin‐trypsin. The content of 17 amino acids of DSCH was detected by precolumn derivatization RP‐HPLC. Using Franz diffusion cell systems studied the transdermal effect of DSCH and then examined the percutaneous rate and molecular weight distribution of percutaneous proteins (PP). Further, we studied the bioactivity of PP in vitro, such as the total antioxidant capacity and collagen secretion in NIH/3T3 cells. Results: About 8.0% DSCH could penetrate skin of mouse, the molecular weight of PP mainly distributed in 5 ~ 13 kDa, accounted for 91.55%. Compared with the antioxidant activity of DSCH, PP had obvious antioxidant activity of scavenging radical cation. Meanwhile, PP promoted cell proliferation and collagen I secretion in fibroblast cells; however, level of type III collagen has no change. Conclusion: Collagen hydrolysates of deer sinew may be used as cosmetic material to protect the skin from oxidative stress, to prevent premature skin aging.